A reversal of fortune: Comparison of health system responses to COVID-19 in the Visegrad group during the early phases of the pandemic. Issue 5 (May 2022) - Sagan, Anna; Bryndova, Lucie; Kowalska-Bobko, Iwona; Smatana, Martin; Spranger, Anne; Szerencses, Viktoria; Webb, Erin; Gaal, Peter
Highlights: The Visegrad countries mitigated the first COVID-19 wave with harsh preventive measures. Once the initial spread was suppressed, the countries did little to prevent further surges. Politics and economic considerations explain reluctance to maintain or tighten restrictions. All four countries paid a high price in terms of direct and indirect death toll related to COVID-19. Abstract: This paper analyses the health policy response to the COVID-19 pandemic in the four Visegrad countries – Czechia, Hungary, Poland, and Slovakia – in spring and summer 2020. The four countries implemented harsh transmission prevention measures at the beginning of the pandemic and managed to effectively avoid the first wave of infections during spring. Likewise, all four relaxed most of these measures during the summer and experienced uncontrolled growth of cases since September 2020. Along the way, there has been an erosion of public support for the government measures. This was mainly due to economic considerations taking precedent but also likely due to diminished trust in the government. All four countries have been overly reliant on their relatively high bed capacity, which they managed to further increase at the cost of elective treatments, but this could not always be supported with sufficient health workforce capacity. Finally, none of the four countries developed effective find, test, trace, isolate and support systems over the summer despite having relaxed most of the transmission protection measures since late spring. This left the countries ill-prepared for the rise in the number of COVID-19 infections they have been experiencing since autumn 2020.